SHAPU: Forty years on Mystery Persists - Upadhyay, Madan P; Shrestha, Bharat R (Nepalese Journal of Ophthalmology, 2017)
In 1975, our team encountered several cases of severe inflammatory eye disease presenting as a white pupil in a red eye with rapid loss of vision. The eyes became soft within a few days with shallow anterior chamber which we called “Malignant Hypotension” in view of the latter’s sinister significance. Unilaterally, little or no pain, predominantly affecting children and difficulty in dilating the pupil and keeping it dilated were some of the other important features. Posterior segment was not visible due to massive exudation in vitreous. Microbiological investigations of aqueous humor did not retrieve any bacterial or fungal organisms. All eyes became pthisical in few weeks despite treatment with topical and subconjunctival antibiotics and steroids. Similar cases appeared again after two years in 1977 with identical presentation and outcome. Both out breaks began during September and lasted until about January- the next year.